SOCIAL EXCLUSION OF DEMI-MONDAINE AND NYAI IN FRENCH AND INDONESIAN NOVELS - Arifah Arum Candra Hayuningsih (Jurnal Poetika, 2021)
One of the interesting themes but not widely featured in Indonesian and French literatures in the 19th and 20th centuries is nyai and demi-mondaine. Both have a similar meaning, namely the mistress of a man from the upper-middle class. This study looks at the exclusions that occur in the lives of nyai and demi-mondaine in an Indonesian novel titled Bumi Manusia by Pramoedya Ananta Toer and a French novel titled La Dame aux Camélias by Alexandre Dumas (philosophers). The analysis was carried out using Fairclough’s critical discourse analysis approach to examine the exclusion process in the two novels, which describes the realities that occur in society. This study found that the mistresses are excluded primarily through labeling and stereotyping. Despite the exclusion from the discourse of ‘honor’ in society, the mistresses find their own way of surviving in a society that does not like them.